Development of Mathematics Educational Games Through PowerPoint for Early Childhood - Lisa Rosalina (JOYCED: Journal of Early Childhood Education, 2022)
This research has entitled the development of mathematics educational games in the form of power points for children aged 5-6 years to produce learning media that attract children's interest in mathematics learning at Muthiah Islamic School Kindergarten, Kayuagung. This development uses a combination of the Alessi & Trollip model and formative evaluation from Tessmer. Data collection techniques use expert reviews, interviews, and observations. The results showed that the one-to-one evaluation stage obtained an average of 86% of children's observation results on eight themes with very good categories, so the product was declared practical and easy to use for children. Meanwhile, in the small group evaluation stage, the average results of children's observations on eight themes were obtained by 92% with excellent categories. From all the stages that have been carried out, it can be concluded that mathematical educational games in the form of power points are declared valid and practical for children.